Compressibilidade de um Argissolo Amarelo distrocoeso submetido a diferentes manejos Compressibility of an Ultisol submitted to different managements - Veronildo S. Oliveira; Mário M. Rolim; Yuri D. J. Costa; Elvira M. R. Pedrosa; Ênio F. de F. e Silva (Revista Brasileira de Engenharia Agrícola e Ambiental)
O objetivo deste trabalho foi avaliar a compressibilidade de um Argissolo Amarelo distrocoeso submetido a diferentes sistemas de manejo sob cultivo de cana-de-açúcar. O experimento foi realizado em áreas da Usina Triunfo Industrial, AL, onde se avaliaram os manejos: MA - mata nativa; MSI - manejo sem irrigação; MCI - manejo com irrigação e MCV - manejo com fertirrigação (vinhaça). Todas as áreas estudadas, exceto no MA, vêm utilizando o preparo convencional do solo com uso de grades pesadas. As amostras de solo foram coletadas nas profundidades de 0-20 e 20-40 cm. Trincheiras foram abertas nas quatro áreas de manejo em estudo, quando amostras de solo indeformadas foram retiradas com auxílio de aneis metálicos de 6,4 cm diâmetro e 2,5 cm de altura em cada profundidade. Após coletadas, as amostras foram saturadas e submetidas a sucções de 0,1 a 10 kPa; 50, 500 e 1500 kPa, levadas à prensa mecânica e realizado o ensaio de compressibilidade. A partir dos dados obtidos determinou-se a tensão de preconsolidação (σp) das diversas amostras ensaiadas, cujos resultados foram submetidos à análise de regressão para a variável tensão de preconsolidação, em função da sucção matricial do solo. Em todos os manejos, a profundidade de 0-20 cm mostrou ser a mais susceptível à compactação em relação à profundidade de 20-40 cm; o manejo MCV alterou o comportamento compressivo do solo em ambas as profundidades (0-20 e 20-40 cm) e a capacidade de suporte do solo foi maior em todos os manejos, nas camadas de 20-40 cm. The objective of this paper was to evaluate the compressibility of an Ultisol submitted to different managements of sugarcane cultivation. The investigation was carried out at Triunfo Mill, in the State of Alagoas, Brazil. The testing area was composed by four distinct sub-areas: a preserved forest (NF), an area without irrigation (MWOI), an irrigated area (MWI), and an area with vinasse (MWV). All investigated areas, except the forest, were prepared using conventional equipment for soil preparation. Soil samples were collected within depths ranging from 0 to 20 cm, 20 to 40 cm, and 40 to 60 cm. A trench was dug in the four selected areas and four undeformed samples were collected in each depth. The samples were collected with metallic rings with dimensions of 6.4 cm in diameter and 2.5 cm in height. In the laboratory, the samples were previously saturated and submitted to soil suctions raging from 0.1 to 1500 kPa in order to build the soil-water characteristic curves. Confined compression tests were performed with saturated samples. The results obtained from the compression tests were used for the determination of the void ratio (e) and the pre-consolidation stress (σp) of the tested samples. Data were submitted to regression analysis and the differences among the obtained means were compared using the test of Tukey at 5% of probability. Regression analysis for pre-consolidation stress in function of water content (Ug) and correlations among the several variables were carried out at 5-% significance. Within all investigated areas, the depth range from 0 to 20 cm showed to be more susceptible to compaction in relation to the depth range from 20 to 40 cm. Management MWV was found to modify the compressive behavior of the soil in both depth ranges. In all investigated areas, the soil bearing capacity was higher in the depth range of 20 to 40 cm.